Influence of pore structure features on the high temperature tensile strength of coke - GUO Wen-tao; XUE Qing-guo; LING Chao; ZUO Hai-bin; WANG Jing-song; HAN Yi-hua (工程科学学报)
Through measuring the pore structure features of coke reacted with H2O or CO2 using a mercury porosimeter,the influence of average pore size,specific surface area and pore size distribution on the high temperature tensile strength of coke were studied in this paper. It is found that the porosity and average pore diameter of coke increase with the increase of reaction degree. When the average pore size is less than 30 μm,the gasification reaction is mainly pore-creating,and the surface area of coke increases firstly and then decreases with increasing reaction degree; but when the average pore size is more than 30 μm,the gasification reaction is mainly pore-expanding. Compared with CO2,coke reacted with H2O has a smaller average pore diameter,larger specific surface area and tensile strength. The tensile strength of coke decreases with the increase of porosity and average pore diameter. At an average pore diameter smaller than 30 μm,the tensile strength decreases with the increase of specific surface area; but at an average pore diameter larger than 30 μm,the tensile strength decreases with the decrease of specific surface area. The small pore increases the tensile strength of coke,while the large pore decreases the tensile strength. At the same reaction rate,coke reacted with H2O has a large amount of small pores and large specific surface area,which are conducive to protect the structure of the air pore wall and to prevent from the reduction of tensile strength at high temperature.